L-Asсorbic acid as an important antioxidant and signal-regulatory agent in the cells of higher plants - Vaitsiakhovich, Maryia A.; Kuchinskaya, Victoria A.; Navaselsky, Ilya Yu.; Hryvusevich, Palina V.; Samokhina, Veranika V.; Mackievic, Viera S.; Sokolik, Anatoly I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2019)
This work provides an overview of data regarding ascorbic acid as an essential antioxidant and regulating agent in physiological processes in plants. The biosynthesis of ascorbate in plants occurs via several pathways; it also has its specific systems for membrane transport. The participation of ascorbate in the antioxidative defence mainly comes down to its role in the Foyer – Halliwell – Asada cycle, which is used to neutralize hydrogen peroxide within all intracellular compartments (with the exception of the cell wall). Some recent papers point to the direct involvement of ion channels in the transportation of ascorbate anions. There is evidence of ascorbate’s previously unexplored functionality, such as absorption and metabolism of iron, as well as regeneration of redox-signals. The pro-oxidant aspect of ascorbate has not yet been studied in-depth; however, some researchers consider it to be capable of taking part in the synthesis of hydroxyl radicals within both normal and stress conditions. Some of the potential areas of research for the future works pertaining to this topic could include the further specification of ascorbic acid’s ability to serve as a reducing agent for iron upon its uptake by the roots, as well as its role in the induction of Са2+-signals, which participate in the regulation of stress and hormonal responses.
Keywords: L-ascorbic acid; higher plants; Arabidopsis thaliana (L.); antioxidant and prooxidant role; Ca2 -signals; signal-regulatory agent; hydroxyl radical